1964
DOI: 10.2466/pr0.1964.15.2.479
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Analysis of Analogical Reasoning

Abstract: Previous studies of analogical reasoning leave two important questions unanswered: (1) What does analogical reasoning consist of as a process? (2) What do analogy tests test? The purpose of the studies described in this paper was to investigate the process of analogical reasoning under conditions which control for hypothesized confounding effects of word association. The results suggest that approximately half the analogy items on current tests can be solved by word association; a new analogy test minimally so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1969
1969
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Since the associations that a stimulus element has or acquires are likely to determine whether it will function as a cue, elements already having a common associa-tion structure for subjects of a given age might be the best potential source of cues. Willner's (1964) finding that many analogy items on standard tests can be solved by free association suggested a means for pitting correct abstract reasoning against the tendency to respond to cues on the basis of strong associations. Willner showed that, given only the third word of analogy items as a stimulus, people frequently respond with the correct answer to the analogy as their first association.…”
Section: General Methodsmentioning
confidence: 99%
“…Since the associations that a stimulus element has or acquires are likely to determine whether it will function as a cue, elements already having a common associa-tion structure for subjects of a given age might be the best potential source of cues. Willner's (1964) finding that many analogy items on standard tests can be solved by free association suggested a means for pitting correct abstract reasoning against the tendency to respond to cues on the basis of strong associations. Willner showed that, given only the third word of analogy items as a stimulus, people frequently respond with the correct answer to the analogy as their first association.…”
Section: General Methodsmentioning
confidence: 99%
“…One seldom-controlled feature of tests of human analogical reasoning is that the correct answer is often a closer associate of the B term than is the incorrect answer (see Willner, 1964). The present experiment controlled for associations between the B term of the analogy problems and the answer alternatives with a procedure similar to that of Experiment IB.…”
Section: Experiments 3amentioning
confidence: 99%
“…The puppet uses an arrow as a prop when looking at the analogy cards. I n order to avoid constructing analogy items that could be solved by simple word association -an issue noted by Willner (1964) -possible items for the C term were listed and presented to sixth grade students who were asked to write the first thing they thought of when they read each word. Any pair generated by word association was not used as the final pair of an analogy.…”
Section: Methodsmentioning
confidence: 99%